Family Caregivers Employed by Home Care Agencies: Lessons Learned From Switzerland and the United States - Iren Bischofberger; Mary Jo Vetter (Frontiers Media S.A., 2023)
Background: Increasing demands for home care staff has been triggered in the past decades by shorter hospital length of stay, and a shift of responsibility for complex care regimens to private households. Therefore, an innovative model to employ family caregivers in home care agencies is expanding in Switzerland and the United States. This policy brief aims to identify core characteristics of the model and analyze its potential benefits and challenges.Evidence: The model is expanding based on legal ground but without the requisite scientific evidence. After an initial patient assessment by a registered nurse, and assigned hands-on tasks to family caregivers, the salary is derived from payer reimbursement.Policy Options and Recommendations: Standards need to be in place to determine the family caregivers qualification that are specific to the client situation of all age groups. Supervision of quality of care, labor law, and blurred roles of biographical relationships remains at the responsibility of the home care agency.Conclusion: Further research for the data-driven exploration of the model is needed to inform the many stakeholders involved.